Reinterprestasi Hadis Mesoginik Kepemimpinan Wanita Dalam Musnad Ahmad Perspektif Maqasid Al-Shariah
Misogynistic Hadith Reinterpretation of Women’s Leadership in Musnad Ahmad Maqasid Al-Shariah Perspective This article aims to reinterpretation the mesoginic hadiths that describe women’s leadership in Ahmad’s musnad of the maqasid al-shariah perspective. The leadership of Muslim women in the public sphere has indeed experienced a significant development in recent years. But in some Muslim circles, women’s leadership in the public sphere is still a taboo and is still clashed with mesoginic hadiths that describe women’s leadership. In this study, the method used is a qualitative descriptive method of the library research type. The use of qualitative descriptive methods due to their suitability with the subject matter and focus of the research. The study found: 1) The mesoginic hadith when analyzed using the maqas